Penerapan Planning, Organizing, Actuating, And Controlling (POAC) Dalam Manajemen Bisnis Islam - Sinta Sukma Ayu; Zuhrinal M. Nawawi (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This research aims to determine the application of Planning, Organizing, Actuating, and Controlling (POAC) in Islamic Business Management. This research uses a qualitative research method with a Systematic Literature Review (SLR) approach. The existing data sources come from indexed journal literature that has an ISSN (International Standard Serial Number) electronically which has been published via the internet with the code E-ISSN. Data collection was carried out via internet surfing from Google Scholar. The research data population is journals and books that focus on POAC (Planning, Organizing, Actuating, and Controlling). The results of this research state that the implementation of planning in Islamic business management must be in line with sharia values, ensuring that business objectives not only benefit the company, but also create social and economic benefits for society as a whole. The application of organizing in Islamic business management involves the creation of a fair and sustainable organizational structure. The separation of duties and responsibilities must reflect fairness, and strategic decisions must take into account their impact on society. Synergy between business interests and general welfare is the main key in the organizing process. The application of actuating in Islamic business management is the implementation of Islamic values in every company action such as work ethics, transparency and honesty and creating fair economic opportunities. The application of controlling in Islamic business management includes continuous monitoring of compliance with sharia principles. This includes ongoing evaluation of business sustainability and fair distribution of profits. Controls also ensure that the business operates in accordance with Islamic objectives and does not involve practices that are inconsistent with sharia law.